The Effect of Sustainability Report Disclosure Compliance on the Company's Financial Performance - Masyhuri Hamidi; Amelia Rahmadhani Putri Amrigan; Fajri Adrianto (Journal of Social Research, 2023)
The issue of the sustainability of a company today is very important. Where the company must think ahead how the business carried out can be beneficial not only for internal but also external companies at this time and in the future. This study aims to determine the effect of compliance on sustainability reports disclosure on financial performance as measured using the Tobin's Q ratio. The sample in this study were all companies that received bronze to platinum ratings on ASRRAT for the 2018-2021 period and were listed on the stock exchange. This data is processed using panel data regression. The results of this study are that economic disclosure has a negative effect and significant, environmental disclosure has a negative effect but not significant, while social disclosure has a positive effect and significant.